Multiobjective problems with fuzzy parameters and games against nature - Larbani, Moussa (Elsevier, 2010)
In the present paper a multiobjective problem with fuzzy parameters is investigated. A two person zero-sum multiobjective game with the first player as the decision maker and the second as Nature, and -cuts are used to introduce a concept of solution for this problem, the Pareto-Maxmin solution. An interactive procedure for the computation of the introduced solution is provided as well.